2008
DOI: 10.3748/wjg.14.70
|View full text |Cite
|
Sign up to set email alerts
|

Genetic changes of p53, K-ras, and microsatellite instability in gallbladder carcinoma in high-incidence areas of Japan and Hungary

Abstract: It appears that the p53 mutations and MSI differ in patients with gallbladder carcinoma between two distinct high-incidence areas. Geographic variation might exist in the process of gallbladder carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 37 publications
4
49
3
Order By: Relevance
“…Inactivation of the TP53 gene is among the most frequent genetic alterations in human malignancies and is thought to play an important role in the pathogenesis of many malignancies (Greenblatt et al, 1994). Although the reported frequency of TP53 mutation in GBC varies widely (ranging from 31 to 70%), most studies report a frequency greater than 50% (Takagi et al, 1994;Yokoyama et al, 1998a;Moreno et al, 2005;Nagahashi et al, 2008). The frequency of TP53 mutation in this study (50% in Bolivian cases) is comparable with the reported figures.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Inactivation of the TP53 gene is among the most frequent genetic alterations in human malignancies and is thought to play an important role in the pathogenesis of many malignancies (Greenblatt et al, 1994). Although the reported frequency of TP53 mutation in GBC varies widely (ranging from 31 to 70%), most studies report a frequency greater than 50% (Takagi et al, 1994;Yokoyama et al, 1998a;Moreno et al, 2005;Nagahashi et al, 2008). The frequency of TP53 mutation in this study (50% in Bolivian cases) is comparable with the reported figures.…”
Section: Discussionsupporting
confidence: 79%
“…These findings indicate the possibility that there are common factors in the development of GBC between Bolivian patients and Chilean patients. Our aims, therefore, were to examine the frequency of TP53 and K-ras mutations in Bolivian patients with GBC and to compare them with our previous data obtained in other high-GBC-prevalence countries, namely Japan, Chile, and Hungary (Yokoyama et al, 1998a;Nagahashi et al, 2008), to elucidate the pathogenic mechanisms involved in the development of GBC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinoma of gallbladder is an aggressive malignancy and usually presenting at an advanced stage. It ranks fifth among the gastrointestinal malignancy [3] . Its incidence steadily increases with age and women are affected two to six time more than men [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The PCR products of exons 7, 8 and intron 7 of p53 and RT-PCR products of p21 were sequenced directly by Shanghai Sangon Biological Engineering Technology & Services Co,. Ltd. (11). The sequence equipment was ABI PRISM 3730.…”
Section: Introductionmentioning
confidence: 99%